Comparing the disk-diffusion and agar dilution tests for Neisseria gonorrhoeae antimicrobial susceptibility testing. Issue 1 (December 2016) - Liu, Hsi; Taylor, Thomas; Pettus, Kevin; Johnson, Steve; Papp, John; Trees, David
Abstract Background We assessed the validity of testing for antimicrobial susceptibility of clinical and mutantNeisseria gonorrhoeae (GC) isolates by disk diffusion in comparison to agar dilution, and Etest® (bioMerieux, France), respectively, for three third generation extended spectrum cephalosporins (ESC): ceftriaxone (CRO), cefixime (CFX), and cefpodoxime (CPD). Methods One hundred and five clinical isolates and ten laboratory-mutants were tested following Clinical Laboratory Standard Institute (CLSI) and manufacturer's standards for each of the three methods. The measured diameters by the disk diffusion method were tested for correlation with the MIC values by agar dilution. In addition, comparisons with the Etest® were made. Categorical results for concordance, based on standard CLSI cutoffs, between the disk diffusion and the other two methods, respectively, were tested using the Chi-square statistics. Reproducibility was tested for CFX across a 6-month interval by repeated disk tests. Results Across all 115 specimens, the disk diffusion tests produced good categorical agreements, exhibiting concordance of 93.1%, 92.1%, and 90.4% with agar dilution and 93.0%, 92.1%, and 90.4% with Etest®, for CRO, CFX, and CPD, respectively. Pearson correlations between disk-diffusion diameters and agar dilution MIC's were -0.59, -0.67, and -0.81 for CRO, CFX, and CPD, respectively. The correlations between disk diffusion and Etest® were -0.58, -0.73, and -0.49. Pearson correlation between the CFX disk readings over a 6-month interval was 91%. Conclusions Disk diffusion tests remain to be a useful, reliable and fast screening method for qualitative antimicrobial susceptibility testing for ceftriaxone, cefixime, and cefpodoxime.